Health is wealth (Volume 3) - Makasa, Emmanuel Malabo (European Investment Bank, 2019)
Surgical intervention saves lives, but health policies in the developing world have often been too feeble or too focused on treating specific emergencies, rather than ensuring that everyone has access to true universal healthcare. Many rural areas in Africa still have high maternal and infant death rates because there are no local surgeons. Many children drop out of school because their untreated disabilities prevent them from walking the long distances to classes. Surgery can help women who suffer after prolonged childbirth or restore eyesight for the elderly suffering from cataracts. Management of congenital disabilities such as a cleft palate guarantees better nutrition for kids. Investing in healthcare and better surgical capacity enables countries to improve the overall quality of life and avoid discrimination, but it also creates well-paid, respectable jobs and helps the economy. Emmanuel M. Makasa, a Zambian surgeon and representative to the United Nations, has been fighting for years to make surgery accessible to everyone. He has a special interest in providing surgical access to rural communities in the developing world as well as helping physically challenged people lead a better life. This is the third essay in the Big Ideas series created by the European Investment Bank. The EIB is inviting international thought leaders to write about the most important issues of the day. The essays are a reminder that we need new thinking to protect the environment, promote equality and improve people's lives around the globe.